Research Article a Local Yogurt was suggested to be an Antimicrobial Agent for Treating Oral Infection - Hasan, Hamid Ghaffoori; N. Dora babu, (International Journal of Psychosocial Rehabilitation, 2020)
A biological and chemical assays has been applied for studying the activity of an extracted active gradient from Iraqi (Kurdistan) local yogurt and it was used as antibacterial against pathogens isolated from oral infection. Gram (+ve) and gram (-ve) species were isolated and identified using Pincus protocol. The isolates preserved on nutrient agar at 370C and then cultured on a new culture media. Nutrient broth has been supplemented with 15% glycerol for long preservation so that the isolates maintained frozen for several months. Whey protein was precipitated from the local yogurt using 10% TCA solution. The precipitated protein shows a strong inhibitory effects on the isolates growth, the pathogen Proteus mirabilis